Factors that can influence the Total Quality Management (TQM) at Pejabat Felda Wilayah Segamat / Nurul Atika Mahat and Nurul Atikah Abdul Hadi - Mahat, Nurul Atika; Abdul Hadi, Nurul Atikah (2014)
Quality is an integral part of much organization management, and thus the impact of quality is an important aspect for both individual employees and the organizations in which they work. This research focuses on the factors that can give impact and influence the Total Quality Management (TQM) at Pejabat Felda Wilayah Segamat. This research will carefully examine whether quality’s factors such training, organization culture, teamwork and leadership styles may contribute to the Total Quality Management (TQM) in an organization. For these research purposes, 48 questionnaires were distributed and all of the respondent are well managed to return back the entire questionnaire. Simple random sampling is used where all the employees at Pejabat FELDA Wilayah Segamat has an equal chance of being chosen as the respondent. There have three main objectives for this research. First objective is to determine the relationship between training, organization culture, teamwork and leadership with Total Quality Management (TQM). Second objective is to determine the most factors that influence Total Quality Management (TQM). And for the last objective is to measure the level of each factor that influence employee’s performance. The researcher have also used SPSS program version 21.0 where the researcher have used reliability analysis, frequency analysis, descriptive analysis, correlation and also regression analysis. At the end of this studies, the researchers have provided several recommendations regarding the factors that can influence Total Quality Management (TQM).